Compteromesa Sӕther (Diptera, Chironomidae, Prodiamesinae) newly recorded in China with the description of a new species - Shi, Jianyu; Niitsuma, Hiromi; Tang, Hongqu (Zootaxa, 2021)
Compteromesa haradensis Niitsuma et Makarchenko, 1997 is redescribed based on the male adults, pupae and larvae collected from China. Supplemental data are provided here for emending the previous inaccurate descriptions. In addition, a new species, Compteromesa biramosa Tang et Niitsuma, sp. n., is described based on a single male with peculiar morphological features from Yunnan Province, China, tentatively as a member of Compteromesa, which is characteristic in having bare wings and bilobed gonostyli.